Investigation on the applicability of low impact development in DLSU Laguna Campus using stormwater management model - Frias, Rey Angelo G. (Animo Repository, 2021)
Unlike in developing countries, sustainable urban stormwater management has been practiced in developed countries for many years. Facing different challenges such as limited resources and movement, the Philippines is slowly adapting the current global technologies to address existing and future water issues. One technique is the use of Low impact development (LID). It can mitigate the worsening water shortages, uncontrollable surface runoff and degrading water quality while not sacrificing urban development. In this study, a step-by-step procedure was provided and divided into five major parts namely, (1) data gathering, (2) processing of data, (3) modeling and simulations, (4) results from Stormwater Management Model (SWMM), and (5) analysis of results. A total of 810 scenarios were formulated to investigate future water problems that might occur in a developing area like De La Salle University – Laguna (DLSU-L). The scenarios were composed of three delineated sub catchments produced using ArcMap, five different rainfall intensities (60th, 70th, 80th, 90th, and 95th percentile) produced from a processed rainfall data, eight LID technologies (bioretention cell, infiltration trench, rain garden, green roof, permeable pavement, rain barrel, rooftop disconnection, vegetative swale) available in SWMM, and the conventional stormwater management approach or the approach without the use of LID that serves as the baseline scenario. A term called green-gray ratio (GG ratio) or the ratio of pervious area to impervious area was also used as the final parameter to assess the most effective LID control for DLSU-L in terms of reduction in runoff, increase in infiltration, and capacity to store excess stormwater. Overall, results showed a 12% to 80% runoff reduction, and 0% to 55% increase in infiltration in using LID while the increase and decrease of water diverted into and from the LID storages depend on the type of LID applied. Also, based from the analysis, the rainfall intensity and percent imperviousness of a sub catchment were both directly correlated to the total runoff and inversely correlated to the total infiltration. Among these eight LID controls, infiltration trench (IT) showed the best results in terms of runoff reduction, increasing infiltration capacity and GG ratio. IT only needs a 9:1 GG ratio for the first and third sub catchment and 1:1 GG ratio for the second sub catchment to distribute equally the precipitation to total runoff, and total infiltration plus storage at 90th percentile rainfall. It was also found out that in all the scenarios applied, the optimum GG ratio was 11:5 wherein increasing the green space of an area only adds little to no reduction in runoff and increase in infiltration. This study will serve as a guide for future research in the early phase of their LID study and would help advance the knowledge in the country’s water sector. This research, in line with the sustainable development goals (SDGs) can also be the initial step to improve the rules and regulations in protecting and conserving water resources by having an adaptive urban stormwater management system in the country.